The Activities of Torch Ginger Flower (Etlingera elatior) Ethanol Extract on Degradation of Porphyromonas gingivalis Biofilm as Periodontal Pathogen - Devi Anisya Putri; A. Haris Budi Widodo; Meylida Ichsyani; Rifda Naufalin; Oedjijono - (Journal of Indonesian Dental Association, 2023)
Introduction: Porphyromonas gingivalis is bacteria that can form biofilms as the main cause of periodontitis. Mouthwash therapy in long term can cause mucositis and even oral cancer. Antibacterial potential of torch ginger flower (Etlingera elatior) can be developed as an alternative adjuvant therapy for periodontitis. Objective: Aims of this research was to determine the effect of torch ginger flower ethanol extract against degradation of P. gingivalis biofilm. Methods: This research used ethanolic extract of torch ginger flower with concentrations 1.56 mg/mL, 3.125 mg/mL, 6.25 mg/mL, 12.5 mg/mL, 25 mg/mL, and 50 mg/mL. Chlorhexidine gluconate 0.2% was used as positive control and DMSO 1% was used as negative control. Measurement of P. gingivalis biofilm degradation used microtiter plate assay with crystal violet 1% staining which reads its optical density at wavelength of 450 nm. Data were analyzed by one way ANOVA and Post hoc LSD. Results: The percentage of P. gingivalis biofilm degradation with torch ginger flower ethanol extract sequentially were 12.47%, 30.56%, 57.12%, 71.36%, and 74.83%. The analysis showed that there was a significant difference (p<0,05) between treatment groups torch ginger flower ethanol extract, as well as between torch ginger flower ethanol extract with DMSO 1% and chlorhexidine gluconate 0.2%. Optimum concentration of ethanol extract of torch ginger flower on P. gingivalis biofilm degradation was 25 mg/mL and showed no significant difference with chlorhexidine gluconate 0,2% (p>0,05). Conclusion: Conclusion of this research is torch ginger flower (Etlingera elatior) ethanol extract has P. gingivalis biofilm degradation activity.biofilm